2021
DOI: 10.3389/fmicb.2021.615328
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacilli Inhibit Salmonella Biofilm Formation Without Killing Planktonic Cells

Abstract: Salmonellosis is a foodborne infection caused by Salmonella. Domestic poultry species are one of the main reservoirs of Salmonella, which causes the foodborne infection salmonellosis, and are responsible for many cases of animal-to-human transmission. Keeping backyard chickens is now a growing trend, increasing the frequency of direct contact with the flock and, by consequence, the incidence of Salmonella infections. Bacillus subtilis KATMIRA1933 and Bacillus amyloliquefaciens B-1895 are probiotic bacilli that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 57 publications
0
24
0
2
Order By: Relevance
“…It has been shown that CFS of Bacillus subtilis can inhibit enteric pathogens such as ETEC and Salmonella typ. [ 43 , 44 ]. However, in our study, CP9 appeared to display an antimicrobial effect via contact-dependent inhibition and, in parts, via metabolic influence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CFS of Bacillus subtilis can inhibit enteric pathogens such as ETEC and Salmonella typ. [ 43 , 44 ]. However, in our study, CP9 appeared to display an antimicrobial effect via contact-dependent inhibition and, in parts, via metabolic influence.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the idea that some derivatives present in B. subtilis natto supernatant may have antibiofilm activity against E. faecalis . Consistent with this idea, some derivatives of Bacillus species have been shown to inhibit the formation of biofilms by several bacterial pathogens ( Rivardo et al, 2009 ; Yoo et al, 2019 ; Tazehabadi et al, 2021 ). Rivardo et al (2009) found that biosurfactants secreted by B. subtilis and B. licheniformis can effectively inhibit biofilm formation of Escherichia coli and S. aureus .…”
Section: Discussionmentioning
confidence: 71%
“…This trait enables them to have higher acid tolerance and better stability during heat processing and low-temperature storage than other bacteria ( Elshaghabee et al, 2017 ). In addition, previous studies ( Piewngam et al, 2018 ; Tazehabadi et al, 2021 ) have shown that some Bacillus species possess the ability to inhibit the colonization and biofilm formation of pathogens via actions, such as interference with quorum-sensing signals, or production of antimicrobial agents, such as bacteriocin proteins. Piewngam et al (2018) found that probiotic Bacillus subtilis can produce the lipopeptide fengycin for decolonization of methicillin-resistant Staphylococcus aureus (MRSA) in mouse feces and intestines via interference with S. aureus agr quorum-sensing signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of SE attachment to the intestinal epithelial cells by cultured medium from B. subtilis NC11 was also reported by Thirabunyanon and Thongwittaya (2012) . A recent study revealed that Bacillus strains have the potential to inhibit SE biofilm formation by producing the bacteriocin subtilosin A and subtilin ( Tazehabadi et al., 2021 ). These direct SE exclusion mechanisms may contribute to the SE at 3 dpi in this trial.…”
Section: Discussionmentioning
confidence: 99%